Corporate Financial Performance Before, During, and After COVID-19 Activity Restrictions: Evidence for Sustainable Economic Recovery and SDG 8 - Petrus Kanisius Yosta; Baldric Siregar (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The COVID-19 pandemic and activity restriction policies significantly affected the tourism and aviation industries, particularly their financial performance. Although Indonesia revoked activity restrictions in 2022, COVID-19 cases continued to exist, creating both risks and opportunities for business sustainability. This study aims to evaluate differences in corporate financial performance before the COVID-19 pandemic, during the pandemic, and after the lifting of activity restrictions. Method: Employing a quantitative approach using financial data from tourism and aviation companies listed on the Indonesia Stock Exchange (IDX). The sample consisted of 14 companies selected through purposive sampling. Financial performance was evaluated across three periods: before COVID-19 (2017–2018), during COVID-19 (2020–2021), and after activity restrictions were lifted (2022). Data were analyzed using paired sample tests with SPSS. Results: The findings indicate significant differences in corporate financial performance across the three periods. Financial performance was relatively stable before the pandemic, declined substantially during COVID-19 due to activity restrictions, and showed signs of recovery after restrictions were lifted. However, the post-restriction recovery had not yet fully returned to pre-pandemic levels. Novelty: Providing empirical evidence on the comparative financial performance of tourism and aviation companies across pre-pandemic, pandemic, and post-restriction periods. The findings contribute to understanding corporate resilience and recovery strategies while offering insights for sustainable economic recovery in support of SDG 8 (Decent Work and Economic Growth).